1996
DOI: 10.1021/ma9517097
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Patterns of Nearly Critical Gels

Abstract: We measure the complex rheological behavior of nearly critical gels and analyze the data by searching for characteristic patterns and abstracting those patterns into a self-consistent model. The sample is a linear, flexible, nearly monodisperse polybutadiene which gets cross-linked on its vinyl side groups. The dynamic mechanical storage and loss moduli of cross-linking polymers change smoothly during the liquid-solid transition, while equilibrium rheological properties (e.g., zero-shear viscosity and equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 43 publications
12
116
0
2
Order By: Relevance
“…This prediction is in accord with experimental results on crosslinked systems with Z x < 1 [303]. Crosslinking linear chains that are already entangled, however, does indeed lead to a much more striking enhancement of viscosity, consistent with the exponentially slow retraction mode of dangling arms [304,305]. Recent experiments on reacting monodisperse precursor polymers have shown that careful crosslinking of linear segments using a urethane condensation technique does indeed create a much more slowly relaxing melt when Z x > 1, and that, for the systems so far explored up to Z xˆ1 3:6, the dynamic exponent u ' 1=Z x with a prefactor close to unity [306,307].…”
Section: Complex Topologies: the Seniority Distributionsupporting
confidence: 88%
“…This prediction is in accord with experimental results on crosslinked systems with Z x < 1 [303]. Crosslinking linear chains that are already entangled, however, does indeed lead to a much more striking enhancement of viscosity, consistent with the exponentially slow retraction mode of dangling arms [304,305]. Recent experiments on reacting monodisperse precursor polymers have shown that careful crosslinking of linear segments using a urethane condensation technique does indeed create a much more slowly relaxing melt when Z x > 1, and that, for the systems so far explored up to Z xˆ1 3:6, the dynamic exponent u ' 1=Z x with a prefactor close to unity [306,307].…”
Section: Complex Topologies: the Seniority Distributionsupporting
confidence: 88%
“…This argument was confirmed experimentally by Mours and Winters in. 16,17 Another study by Emri 18 also agrees with the observation by Mours and Winters, arguing that high molecular weight (9) T g − T g0…”
Section: Disclosure Statementsupporting
confidence: 69%
“…The stiffness of the critical gels increases with ∆T and the relaxation exponent adopts values of about 0.5 (which is very similar to the relaxation exponent of chemical critical gels from high molecular weight precursors 37 ).…”
Section: Discussionsupporting
confidence: 58%